Understanding sleeplessness : perspectives on insomnia - Neubauer, David N., 1951- (Johns Hopkins University Press, 2003)
"Building on the four perspectives conceptualized by Paul McHugh and Phillip Slavney in The Perspectives of Psychiatry, Neubauer offers a much-needed explanation of the diverse ways of understanding insomnia and what should be done about it. He begins by surveying what is currently known about the mechanisms of "normal sleep" and, in this context, describing the problems of defining, assessing, and measuring insomnia. Drawing examples from patients studied at the Johns Hopkins Sleep Disorders Center, Neubauer then applies each of the four perspectives - diseases, dimensions, behaviors, life stories - to the varied kinds and degrees of sleeplessness. Finally, calling on the full range of perspectives on insomnia, he outlines an integrated approach to evaluation and treatment. His work will be of great interest and value to those who study and treat sleeplessness and to those who wish to understand this widespread and vexing problem."--Jacket.